Mnemonic strategies in teaching English vocabulary communicatively among elementary basic education students at an educational institution in Loja, school year 2023-2024 - Angamarca Quizhpe, Valeria Nicole (2024)
Considering that vocabulary is often deemed as the pillar of the four language skills and an essential component in English Language Teaching and Learning, it is imperative to use and evaluate strategies that can assist in the enhancement of this language component. For that reason, this study aimed to apply mnemonic strategies in teaching vocabulary communicatively, opening the path to determine their effectiveness in vocabulary instruction, and to identify if students develop creative skills while using them. To fulfill these objectives, this action research study was conducted over the course of 6 weeks, using the mixed-method approach. Moreover, the participants were 22 students of elementary basic education, from a public institution in Loja, Ecuador. To gather the necessary data, the researcher used the testing technique, with a pre- and post-test; the survey technique, implementing a questionnaire; and the observation technique, using field notes as the instrument. Consequently, the quantitative data was analyzed using descriptive statistics and the qualitative data using thematic analysis. The data analysis and interpretation showcased that students had clearly enhanced their vocabulary proficiency, starting with an average score of 4.70 out of 10, and raising to 8.41 and that they did develop creative skills when using mnemonic strategies. These findings were all corroborated by the class observations. Overall, it can be concluded that mnemonic strategies are effective in teaching English vocabulary communicatively and that these strategies foster creative skills, prompting students to develop them. Keywords: Mnemonic strategies, Vocabulary strategies, Communicative context, Vocabulary Learning, Creative skills.